Twenty-year clinical experience with fixed functional appliances - Alexandre Moro; Suellen W. Borges; Paula Porto Spada; Nathaly D. Morais; Gisele Maria Correr; Cauby M. Chaves Jr; Lucia H. S. Cevidanes
ABSTRACT Introduction: Considering the large number of fixed functional appliances, choosing the best device for your patient is not an easy task. Objective: To describe the development of fixed functional appliances as well as our 20-year experience working with them. Methods: Fixed functional appliances are grouped into flexible, rigid and hybrid. They are different appliances, whose action is described here. Four clinical cases will be reported with a view to illustrating the different appliances. Conclusions: Rigid fixed functional appliances provide better skeletal results than flexible and hybrid ones. Flexible and hybrid appliances have similar effects to those produced by Class II elastics. They ultimately correct Class II with dentoalveolar changes. From a biomechanical standpoint, fixed functional appliances are more recommended to treat Class II in dolichofacial patients, in comparison to Class II elastics.